Employee satisfaction source of competitive advantage - Jalowska, Anna (Management and Administration Journal, 2023)
Maintaining a competitive position on the market is not an easy task for any entrepreneur. The variety of offers individual institutions causes improvement of products and services is the main responsibility of companies focused on achieving superiority in the sector. The success of an organization is the result of the work of all its employees, regardless of their position, so it is important to create a climate that is conducive to efficient work and affects the level of employee satisfaction. For many, job satisfaction is a priority and a factor increasing engagement, which in turn translates into generated profits and market position.